Use of the Tic in the teaching process to achieve meaningful learning in the students of Peruvian educational institutions of the secondary level - Moreno Sáenz, Jenny Victoria (2016)
The work presented in this article is carried out within the framework of the International Standard ISO 9004: 2009: which is a self-assessment tool to improve the quality of organizations and the proposal of Andrew Churches: The digital taxonomy, based on Taxonomy from Bloom. Both approaches, properly applied, allow efficient use of ICT to achieve meaningful learning in students of regular basic education at the secondary level. The International Standard ISO 9004: 2009 presents a general framework, for the development of this work, only some criteria that have been contextualized for the use of ICT in the teaching process have been taken into account, considering the current educational model of the new design curricular Likewise, the criteria of the norm have been articulated with Bloom's Taxonomy for the digital era, which, when applied, can achieve significant student learning.